Социальные проблемы системы образования - Ейдлін, Р. В. (ХНУРЕ, 2021)
This article focused on analysing the most obvious psychological and pedagogical problems of modern education. A detailed review of the education system identified and articulated certain problems, that have the most negative impact. The result of these issues, such as low participation in lessons, lack of individual attention to each child, overburdening of subjects is a low productivity of learning processes. The research formulated and described certain methods and strategies to overcome these issues and offered advice to educators and learners that would enhance the quality of education.
Keywords: философия; социальные проблемы системы образования